Fault diagnosis for robust inverter power drives - Ginart, Antonio (IET energy engineering series ;, 2018)
This book deals with the concept that the specification of a power component needs a life expectancy associated with other important factors, to allow the appropriate component selection when designing robust and reliable systems. An analysis of the fundamental physics of aging in power drive components and the markers that diagnose the process towards failure is presented to illustrate to the reader state-of-the-art approaches to increase reliability. Amongst the many factors playing an important role in designing a robust power drive, the main factor deals with how long the power drive will last at the conditions in which it will be operating. In particular, the book looks at invertor power drive reliability and diagnosis; power semiconductors, SiC, GaN, MOSFETs and IGBTs; DC-link capacitors; embedded fault diagnosis and prognosis; fault tolerance strategies for power convertors; motor diagnostics and protection using invertor capabilities; battery storage; prognostics with a particular application to a battery.